Compulsory insurance in the provision of insurance protection - L. A. Orlanyuk–Malitskaya (Путеводитель предпринимателя)
The transition to a digital economy in a «risk society» is transforming financial institutions, changing their social significance and strategic development goals. The development of insurance in general, and compulsory insurance in particular, is influenced by two global factors: changing the risk situation, including qualitative changes in the nature of the risk; and the growth of public consciousness in the field of risk management, awareness of the need for insurance protection. Compulsory insurance aimed at protecting the public interest in this situation becomes of particular importance. The structure of threats and new phenomena in the realization of risk require at this stage more than the current state participation in compulsory insurance.